ANALISIS KEMAMPUAN PEMAHAMAN KONSEP METEMATIS PESERTA DIDIK KELAS VIII PADA MATERI BILANGAN BERPANGKAT - Meri Novica; Sri Yunita Ningsih (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2026)
: This study aims to analyze the ability of students to understand mathematical concepts in the material of ranked numbers in grade VIII of SMP Negeri 1 Pasir Penyu. This study uses a descriptive qualitative approach with 30 students. The results showed that the average score on the indicator restated the concept was 2.77, gave examples and non-examples of 2.63, classified objects according to the nature of the concept of 2.60, and applied concepts in problem solving of 1.63. In general, students' ability to understand mathematical concepts is in the medium category, with details of 13.33% of the high category, 66.67% of the medium category, and 20% of the low category. These results show that most of the students already have an understanding of basic concepts, but still experience difficulties in applying concepts, especially in problem solving. Therefore, learning needs to emphasize a deeper understanding of concepts and the development of problem-solving skills.Keywords: understanding of mathematical concepts, ranked numbers, learners